(untitled) (Revista de Estudos da Linguagem, 1993)
Th1s paper discusses some research resulta on sex differences ln the speech of homeless adolescents ln Belo Horizonte. The study showed that male speakers use more standard forms than female speakers, although the inicial hypothesis predicted that groups with a great many characteristics ln common would present little d1fferences concerning prestige forms.